MANAJEMEN PORTOFOLIO SAHAM SYARIAH: STRATEGI OPTIMALISASI INVESTASI BERBASIS PRINSIP SYARIAH - Erni Syufitri; Juliza; Rismawan (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAI ALMUSLIM, 2026)
This research examines the management of Islamic stock portfolios as an alternative investment that combines Islamic Sharia principles with modern portfolio theory. The research aims to analyze the concept, strategies, and implementation of Islamic stock portfolio management in Indonesia. This study uses a qualitative approach with library research methods and content analysis of literature, regulations, and documents related to the Islamic capital market. Data were collected from secondary sources including books, scientific journals, reports from the Financial Services Authority (OJK), fatwas from the National Sharia Council - Indonesian Ulema Council (DSN-MUI), and documents from the Indonesia Stock Exchange (IDX). The results of the study indicate that Islamic stock portfolio management has unique characteristics that distinguish it from conventional portfolios, namely the existence of a sharia screening process, the prohibition of riba, gharar, and maysir, and an orientation towards the halal sector. Diversification, rebalancing, and performance evaluation strategies based on sharia indices such as the Jakarta Islamic Index (JII) and the Indonesia Sharia Stock Index (ISSI) are key to portfolio optimization. This research concludes that Islamic stock portfolio management can provide competitive returns while maintaining compliance with sharia principles, making it a sustainable and ethical investment choice for Muslim investors.